2018
DOI: 10.1177/2381468318776634
|View full text |Cite
|
Sign up to set email alerts
|

Population Health and Cost-Effectiveness Implications of a “Treat All” Recommendation for HCV: A Review of the Model-Based Evidence

Abstract: The World Health Organization HCV Guideline Development Group is considering a “treat all” recommendation for persons infected with hepatitis C virus (HCV). We reviewed the model-based evidence of cost-effectiveness and population health impacts comparing expanded treatment policies to more limited treatment access policies, focusing primarily on evaluations of all-oral directly acting antivirals published after 2012. Searching PubMed, we identified 2,917 unique titles. Sequentially reviewing titles and abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 107 publications
3
40
0
1
Order By: Relevance
“…Moreover, some studies also reported higher rates of SAEs and treatment discontinuation in the elderly . These findings have raised concerns whether a ‘treat all’ strategy is justified given the lack of a comprehensive risk‐benefit analysis in this particular patient population …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, some studies also reported higher rates of SAEs and treatment discontinuation in the elderly . These findings have raised concerns whether a ‘treat all’ strategy is justified given the lack of a comprehensive risk‐benefit analysis in this particular patient population …”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that DAA treatment for HCV is highly effective and safe in patients aged ≥65 years, thereby supporting current guideline recommendations to treat all patients without age restrictions. However, recent data suggest that treatment in elderly patients without significant fibrosis may only be cost‐effective at lower prices . Moreover, there is still insufficient data to predict the long‐term effects of HCV cure and its impact on overall survival in elderly patients, particularly in the absence of advanced fibrosis or cirrhosis, as the progression to cirrhosis may never occur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those who failed treatment were not eligible for re-treatment. Previous studies had suggested that broadly expanded treatment could provide substantial health gains due to the reduced the reinfection risks [18]. In this study, due to the lack of data in China, we made a relatively conservative assumption of the expanding treatment's potential for reducing HCV reinfection as 5% (range: 2.5-7.5%) [5], one-way sensitivity analysis would be conducted to determine its impact on cost-effectiveness.…”
Section: Progression Regression and Reinfection After Svrmentioning
confidence: 99%